Draft genome sequence of Bacillus safensis 2T-2, isolated from drinking waterNCBI Genbank - Cornelius C. Bezuidenhout; Lesego G. Molale-Tom; Rinaldo K. Kritzinger; Oluwaseyi Samuel Olanrewaju (Data in Brief)
Bacillus safensis 2T-2 was isolated from potable water at a municipal water treatment facility in the North West province of South Africa, representing the first report of this species in treated drinking water systems. Whole genome sequencing revealed a 3.78 Mb genome with 41.3 % GC content and 4000 coding sequences distributed across 126 contigs. Genome analysis identified six antibiotic resistance genes, including vancomycin resistance genes (vanT, vanY), fosfomycin resistance (fosBx1), chloramphenicol resistance (cat86), and two disinfectant resistance genes (qacG, qacJ). Despite the presence of resistance genes, PathogenFinder analysis confirmed low pathogenic potential (0.168 probability). The strain demonstrated significant biosynthetic capabilities with 12 secondary metabolite gene clusters, including antimicrobial compound production (plantazolicin), biosurfactants (lichenysin), siderophores (bacillibactin, schizokinen), and the lipopeptide fengycin. Five bacteriocin gene clusters were identified, containing three core peptide genes (UviB, plantazolicin, pumilarin) with associated modification and transport genes. Phylogenetic analysis positioned strain 2T-2 closest to B. safensis F0–36b, confirming species identification. These findings highlight the dual nature of environmental bacteria in water systems, possessing both concerning antibiotic resistance traits and beneficial biotechnological potential, emphasizing the need for enhanced water treatment strategies while revealing opportunities for bioactive compound discovery.